2013
DOI: 10.1038/emi.2013.65
|View full text |Cite
|
Sign up to set email alerts
|

The fibronectin-binding motif within FlpA facilitatesCampylobacter jejuniadherence to host cell and activation of host cell signaling

Abstract: Campylobacter jejuni is a gram-negative, curved and rod-shaped bacterium that causes human gastroenteritis. Acute disease is associated with C. jejuni invasion of the intestinal epithelium. Epithelial cells infected with C. jejuni strains containing mutations in the FlpA and CadF fibronectin (Fn)-binding proteins exhibit reduced invasion of host cells and a C. jejuni CadF FlpA double mutant is impaired in the activation of epidermal growth factor receptor (EGFR) and Rho GTPase Rac1. Although these observations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 42 publications
3
32
0
Order By: Relevance
“…Moreover, the CadF and FlpA proteins, which share only 25.6% similarity at the amino acid level, cannot functionally complement one another as evident in the phenotypic assays performed in this study (e.g., facilitating cell adherence, promoting FN binding, stimulating cell signaling, and enabling effector delivery to host cells). This finding is consistent with the fact that the CadF and FlpA proteins have distinct FN-binding domains [19,20]. Noteworthily, deduced amino acid sequences of the S. aureus FNBPA and FNBPB share a high level (74.2%) of similarity [45], and that complementation of a fnbA fnbB double mutant with either fnbA or fnbB fully restores the FN-binding activity [46].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Moreover, the CadF and FlpA proteins, which share only 25.6% similarity at the amino acid level, cannot functionally complement one another as evident in the phenotypic assays performed in this study (e.g., facilitating cell adherence, promoting FN binding, stimulating cell signaling, and enabling effector delivery to host cells). This finding is consistent with the fact that the CadF and FlpA proteins have distinct FN-binding domains [19,20]. Noteworthily, deduced amino acid sequences of the S. aureus FNBPA and FNBPB share a high level (74.2%) of similarity [45], and that complementation of a fnbA fnbB double mutant with either fnbA or fnbB fully restores the FN-binding activity [46].…”
Section: Discussionsupporting
confidence: 84%
“…Cdc42 and Rac1 are the primary host cell Rho GTPases involved in C. jejuni invasion. We have also reported that Rac1-GTP production is also diminished in human INT 407 cells infected with C. jejuni flpA and cadF flpA double mutant [19]. Given the findings from this study, which demonstrate that CadF and FlpA work together in facilitating cell adherence, promoting FN binding, stimulating cell signaling, and enabling effector delivery to host cells, studies are warranted to determine if disease symptoms arise in animals inoculated with a C. jejuni cadF flpA double mutant.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Since core tryptophan residues are conserved across all FnII domains as well as their ancestral kringle domains, similar studies could help understand their role in protein-ligand interactions of other proteins containing FnII domains and the significance of such interactions. For example, previous studies have shown that infection by many pathogenic bacteria and viruses involves the interaction of their surface protein with the FnII domain of fibronectin on the host and that such binding is necessary for their life cycle [33][34][35]. Comparison of solution structure of FnII domains of fibronectin and PDC-109 shows similar solvent-exposed orientation of a core tryptophan residue [4,6].…”
Section: Discussionmentioning
confidence: 99%